Effects of COVID-19-Related Anxiety and Sleep Problems on Loneliness and Feelings of School Refusal in Adolescents - Okajima, Isa; Honda, Yukako; Semba, Osamu; Kiyota, Yoji; Tani, Yasuo (Frontiers in Psychiatry, 2022)
Background COVID-19-related anxiety, sleep problems, and loneliness may be risk factors for school refusal in children and adolescents. However, few studies have examined the mechanisms by which these risk factors cause school refusal. This study examined the process by which COVID-19-related anxiety, sleep problems, and loneliness cause school refusal, using structural equation modeling. Methods In this cross-sectional questionnaire-based study, 256 (109 male, 147 female, mean age: 15.37 ± 0.48 years) senior high school students were asked to complete the Stress and Anxiety associated with Viral Epidemics-6 questionnaire to assess COVID-19-related anxiety, the Athens Insomnia Scale (AIS), Sleep Debt Index (SDI), and chronotype (MSFsc) to assess sleep problems, the Three-Item Loneliness Scale (TILS) to assess loneliness, and Feelings of School-Avoidance Scale (FSAS) to assess school refusal. Results Structural equation modeling showed that sleep problems affected loneliness (β = 0.52) and feelings of school refusal (β = 0.37), and that loneliness affected feelings of school refusal (β = 0.47). There was no significant pathway of COVID-19-related anxiety on sleep problems, loneliness, or feelings of school refusal. The indirect effect of sleep problems on feelings of school refusal through loneliness was significant. The results of hierarchical multiple regression analysis showed that AIS (β = 0.30) and SDI (β = 0.13) scores were associated with TILS, and AIS (β = 0.26) and MSFsc (β = −0.14) scores were associated with FSAS scores. Conclusion The findings of this study showed that sleep problems affected feelings of school refusal via both direct and indirect pathways through the exacerbation of loneliness. To prevent school refusal in adolescents, addressing the indirect pathway via loneliness could be effective in improving insomnia and sleep debt, while addressing the direct pathway could be effective in improving insomnia and chronotype.